The impact of incorrect disposal of disposable masks: a pandemic 2020 approach (Research, Society and Development, 2022)
This article will bring a brief study about the elements of the fourth industrial revolution and how people are preparing It is necessary to consider the disposal of waste at all levels of its impact, where each segment must build knowledge that allows a non-fragmented view in the act of disposal, collection and awareness of stakeholders. Within this context, the practice of incorrect disposal requires an active legislation, both for the private network and for the population in general, despite being a very important theme, there are still few data scientifically studied and disseminated making the relationship between the pandemic of 2020 and the theme of the article "disposal of disposable masks", so the authors will present a global context of the stages of understanding the concept of logistics, until the impact generated by the incorrect disposal of waste in nature. It was adopted as an additional methodology for grounding the subject: the critical reading of works pertinent to the theme and the verification of the information presented by joining the understanding of other authors. This research found that even in the face of advances in science and the concept of social development and environmental preservation, there is still a major problem to be addressed by this and the next generations who will be responsible for taking care of the decisions made today.